2010
DOI: 10.1371/journal.pone.0012665
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Expression of Ca2+-Permeable ASIC1a Channels in NG2 Glia of Rat Hippocampus

Abstract: NG2 cells, a fourth type of glial cell in the mammalian CNS, undergo reactive changes in response to a wide variety of brain insults. Recent studies have demonstrated that neuronally expressed acid-sensing ion channels (ASICs) are implicated in various neurological disorders including brain ischemia and seizures. Acidosis is a common feature of acute neurological conditions. It is postulated that a drop in pH may be the link between the pathological process and activation of NG2 cells. Such postulate immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 48 publications
(103 reference statements)
0
30
0
1
Order By: Relevance
“…Staining of biocytin‐filled OPCs with Alexa 594‐conjugated streptavidin (1:400; Invitrogen, Carlsbad, CA, USA) was performed as described previously (Lin et al . 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Staining of biocytin‐filled OPCs with Alexa 594‐conjugated streptavidin (1:400; Invitrogen, Carlsbad, CA, USA) was performed as described previously (Lin et al . 2010).…”
Section: Methodsmentioning
confidence: 99%
“…For double immunofluorescence, primary antibodies against NG2 (mouse, 1:200; Abcam), Olig2 (rabbit, 1:500; Millipore, Billerica, MA, USA), glial fibrillary acidic protein (GFAP; rabbit, 1:400; Dako, Glostrup, Denmark), Iba‐1 (rabbit, 1:500; Wako Chemicals, Osaka, Japan) and secondary antibodies (goat anti‐rabbit‐Alexa 488, 1:500 for Olig2, GFAP and Iba‐1; goat anti‐mouse‐Alexa 350, 1:200) for NG2 were used. Slices were imaged by two‐photon microscopy as described previously (Lin et al . 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Almost all neurons possess robust acid-evoked ASIC type current [44-47]. Other than neurons, NG2 glia cells [48], some receptor cells [49-52], vascular smooth muscle [53], and immune cells [54] also express ASICs, though typically at lower levels. In addition, many types of brain tumors upregulate ASIC expression [55,56], which suggests a possible role of ASICs in tumor physiology.…”
Section: Introductionmentioning
confidence: 99%
“…; Lin et al . ; Yang et al . ) and may contribute to acid‐evoked currents and calcium influx in astrocytes (Huang et al .…”
mentioning
confidence: 99%
“…ASIC1A is expressed in neurons and has been located in the soma, axons, dendrites and dendritic spines, where it has been implicated in synaptic transmission and plasticity (Wemmie et al 2002;Zha et al 2006;Zha et al 2009;Du et al 2014;Kreple et al 2014). However, recent studies have suggested that ASICs might also be present in subpopulations of glial cells Feldman et al 2008;Lin et al 2010;Yang et al 2016) and may contribute to acid-evoked currents and calcium influx in astrocytes Yang et al 2016), although relative levels of ASIC1A expression in neurons and nonneuronal cells remain unclear. Most of the tools previously used to manipulate ASIC1A have not discriminated between neuronal and nonneuronal cells.…”
mentioning
confidence: 99%